Peranan Karang Taruna Desa Pasar III Natal Dalam Pembentukan Akhlak Pemuda di Desa Pasar III Natal Kecamatan Natal Kabupaten Mandailing Natal - Akbar, Ahmad (UIN Sumatera Utara, 2023)
This study aims to determine how the role of Karang Taruna in forming good morals towards teenager, especially teenager in Desa Pasar III Natal, Kecamatan Natal, Kabupaten Mandailing Natal. The object of this research is the teenager who participate in the Karang Taruna organization in Desa Pasar III Natal, Kecamatan Natal, Kabupaten Mandailing Natal. The author collects data with qualitative methods through interview and observation techniques that are carried out directly in Desa Pasar III Natal, Kecamatan Natal, Kabupaten Mandailing Natal. The sources in interviews related to this research were: Village Heads, Community Leaders, Head of Teenager Organizations, and Teenager Organizations. All of the informants were asked about how the development of the teenager movement Karang Taruna gave positive values or otherwise. The finding suggests that the teenager of Karang Taruna in Desa Pasar III Natal, Kecamatan Natal, Kabupaten Mandailing Natal were declared to have a positive influence in shaping their character or morals for the better. Karang Taruna provides opportunities for teenager in the formation of good morals through several fields such as the field of religion, the field of social welfare, as well as the field of ownership and responsibility. So overall, the teenager teenager organizations in Desa Pasar III Natal, Kecamatan Natal, Kabupaten Mandailing Natal, have implemented positive activities that can become a forum for teenager moral formation.Keywords: Morals, Teenager, Karang Taruna.